Chekhov in New York: the Functions of Frame in Louis Malle's "Vanya on 42nd Street" (1994) - Dzhumailo, Olga (Slavica, 2019)
This paper focuses on Luis Malle’s creative adaptation of Chekhov’s “Uncle Vanya”. The frame location of "Vanya on 42nd street" is not only documentary evidence and a sign of admiration for the actors' ensemble, creating the spirit of live improvisation in the unfinished theatrical production by Andre Gregory. It is argued that the film is far from being another spectacular 're-citing' of Chekhov's ‘transcultural capital’. A set of framing elements foregrounds Chekhov's art in general and the way he represents Vanya’s stoic endurance in particular as resonating with the living experience of a person of any culture in whatever language (Russian, English, Bengali, theatrical, cinematic, etc.) holds general validity. Among leitmotifs which interconnect the frame and the drama performance within the film there are also those of kinship, unselfish  friendship and true involvement in life as an ongoing rehearsal and improvisation on an inescapable life project that is never successful.